The Experiences and Perspectives of African-Australian Community Service Providers Who Work with At-Risk and Justice-Involved Youth - Shepherd, Stephane (International journal of offender therapy and comparative criminology, 2022)
African-Australian young people are over-represented in custody in the state of Victoria. It has been recognized in recent government and stakeholder strategic plans that African-Australian community service providers are well placed to help address the increasing complex needs of at-risk African-Australian youth. However little is known about the capacities of such providers to effectively contend with this growing social concern. In response, this study aimed to explore the perspectives and operational (service delivery and governance) experiences of African-Australian community organizations which provide services to at-risk young people in Victoria. Through a series of in-depth interviews with the leadership of eight key African-Australian service providers, we aimed to identify their perceived strengths, obstacles faced and proposed strategies to realize key objectives. Perspectives on key risk factors for young African-Australian justice system contact were also gathered. Several themes were extracted from the interviews, specifically (i) Risk factors for African-Australian youth justice-involvement (school disengagement, peer delinquency, family breakdown, intergenerational discord, perceived social rejection), (ii) The limitations of mainstream institutions to reduce African-Australian youth justice-involvement (too compliance focused, inflexible, business rather than human-centered, disconnected from communities and families), (iii) The advantages of African-Australian community service providers when working with African-Australian youth (community credibility, client trust, flexibility, culturally responsive), (iv) The challenges faced by African-Australian service providers (lack of funding/resources, professional staff shortages, infrastructural/governance limitations), and (v) “What works” in service provision for at-risk African-Australians (client involvement in program design, African staff representation, extensive structured programming matched with client aspirations, prioritizing relationship building, persistent outreach, mental health and legal literacy for clients and families). Implications for service delivery and social policy are discussed within.